Pembuatan biopack dari limbah kertas dan daun bagi ibu-ibu pemberdayaan kesejahteraan keluarga dan guru pendidikan anak usia dini - Rahmatullah Rahmatullah; Muhammad Djoni Bustan; Budi Santoso; Harry Waristian; Rizka Wulandari Putri; Rianyza Gayatri (Darmabakti: Jurnal Pengabdian kepada Masyarakat, 2026)
Various creative approaches can be developed to reduce the generation of both organic and inorganic waste. On the other hand, office and school paper waste, as well as plant matter such as dry leaves, are still not being utilized optimally. Biopack is an innovative cardboard container made from a mixture of paper pulp and dry leaves. This product can be used as eco-friendly packaging because it easily degrades when disposed of in soil or water after use. School paper waste and dry leaves available in the Wanaasri Palembang area hold significant potential as raw materials for Biopack. Utilizing this potential is expected to increase public awareness, particularly among the PKK Rumah Cinta Dahlia Wanaasri and the teachers at PAUD Permata Bunda, as key drivers in promoting the innovation of waste management into economically valuable products that can support the establishment of community-based businesses or entrepreneurship. This community service activity was carried out through outreach and a biopack-making demonstration using lectures and hands-on simulations. The evaluation was conducted through a questionnaire to analyze the level of effectiveness and the potential for sustainability of the activity. Survey results from activity participants revealed that 93% were not yet able to recycle used paper and leaves, 63% still disposed of used paper and leaves in trash bins, and 93–100% of participants rated the activity as beneficial, noting that it broadened their knowledge and understanding of making biopack from used paper and leaves, and that they liked the biopack products and were able to use them at home. Furthermore, it is hoped that the Wanaasri community will be able to produce its own biopack, that it will be adopted by teachers at the Permata Bunda Early Childhood Education Center as a teaching aid in the learning process, and that it will eventually be commercialized.